Association of Iron Status in Follicular Fluid with Pregnancy Outcomes in Infertile Women Undergoing IVF/ICSI - Kadhum, Banan Salam; AL- Shammaree, Shatha Abdul Wadood (Iraqi Journal of Science, 2021)
Iron status may influence the outcome of infertile women under the intracytoplasmic sperm injection (ICSI) technique of in vitro fertilization (IVF). The aim of this study is to evaluate iron status and ceruloplasmin ferroxidase activity in the follicular fluid (FF) and their association with IVF outcomes. The study enrolled fertile women with male cause infertility (n=25), infertile women with polycystic ovary syndrome (PCOS; n=21), infertile women with low AMH level (n=26), and women with unexplained infertility (UI; n=27), all undergoing IVF/ICSI. On the day of oocyte suction, the selection of FF samples was accomplished. Iron, ferritin, and transferrin levels, as well as ceruloplasmin (CP) ferroxidase activity, were measured in the FF. In the PCOS group, iron showed significantly higher level (P<0.05) as compared to the control and UI groups. In the PCOS group, ferritin showed significantly higher level (P<0.05) compared with the control group. In the PCOS group, transferrin showed significantly higher level (P<0.05) when compared with the UI group. Also, Cp. ferroxidase activity in the PCOS group showed a lower level, but non-significant difference, compared with the other groups. In conclusion, the increased iron level in the follicular fluid of women with PCOS may lead to decrease pregnancy success after applying IVF protocol.